LADIES PROGRAM: MEDIA KOMUNIKASI PEMBELAJARAN DAN BUDAYA BELAJAR ANTARA ORANG TUA DAN GURU DI SEKOLAH - Fatma Nadiatul Khusna; Deby Fitriana; Novita Nur Amalia; Fitri Puji Rahmawati; Ratnasai Diah Utami (Buletin Literasi Budaya Sekolah, 2021)
Every student essentially can face various difficulties, obstacles, and psychological pressures in carrying out academic activities. Thus, to handle and carry out a preventive attitude towards the academics activities programs, it is necessary to provide a forum as an intermediary between the school and parents, namely the Ladies Programs. This forum is a way to search for information related to students at SD Muhammadiyah Alam Surya Mentari. The Ladies program is a previous program to study. This study aims to determine 1) the description of teacher communication with parents at SD Muhammadiyah Alam Surya Mentari. 2) a communication strategy developed by SD Muhammadiyah Alam Surya Mentari through the ladies program forum. This strategy is a forum implemented by SD Muhammadiyah Alam Surya Mentari to find out the conditions and information related to students. This research is a qualitative approach. The data was by conducting observations and interviews with related parties. Based on the results, it has been that communication between teachers and parents can occur through the Ladies Program forum. SD Muhammadiyah Alam Surya Mentari has several programs to establish communication, such as Cooking Class, Learning by Maestro, and Ladies Programs. This program can be run by involving parents in every activity. The communication strategy is occurring through the Ladies Programs forum, a communication activity forum has held every month and involves the roles of parents and teachers.